2022
DOI: 10.1177/08850666221121734
|View full text |Cite
|
Sign up to set email alerts
|

Increased Endotoxin Activity in COVID-19 Patients Admitted to the Intensive Care Unit

Abstract: Objective Endotoxin is a component of Gram-negative bacteria and can be measured in blood using the endotoxin activity assay (EAA). Endotoxin exposure initiates an inflammatory cascade that may contribute to organ dysfunction. Endotoxemia has been reported in previous viral pandemics and we investigated the extent of endotoxemia and its relationship to outcomes in critically ill patients with COVID-19. Materials and Methods We conducted a Prospective Cohort Study of 96 critically-ill COVID-19 patients admitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Furthermore, longitudinal endotoxin measurements revealed that changes in endotoxemia over time mirrored changes in kidney function. Recent studies have shown that higher EAA levels were associated with AKI in patients with COVID-19 [16, 17]. A small study in 18 patients undergoing cardiopulmonary bypass procedure also demonstrated elevated EAA levels in patients who developed AKI versus those who did not [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, longitudinal endotoxin measurements revealed that changes in endotoxemia over time mirrored changes in kidney function. Recent studies have shown that higher EAA levels were associated with AKI in patients with COVID-19 [16, 17]. A small study in 18 patients undergoing cardiopulmonary bypass procedure also demonstrated elevated EAA levels in patients who developed AKI versus those who did not [20].…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxemia was recently shown to correlate with AKI and requirement for renal replacement therapy (RRT) in critically ill COVID-19 patients [16, 17]. However, the relationship between endotoxemia and kidney function in a broader group of critically ill patients has not been studied.…”
Section: Introductionmentioning
confidence: 99%